A non–financial supply chain performance measurement framework for the Aerospace Division of Rolls-Royce - Cramp, Stephen Anthony (2013)
Rolls-Royce places great emphasis on maintaining a consistent strategy with three main areas at the core of its business identified as being customer, innovation and growing profitability. The ability of the business to deliver on its promises and also putting the customer first is paramount to maintaining growth and securing the future of the company.